ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP PELAKSANAAN RETRIBUSI PARKIR DI KABUPATEN SIDOARJO - AXKY WULANTINA, RISKHIKIA Exky (Jurnal Akuntansi AKUNESA, 2014)
Control system is the physical arrangement of the assembled components in such a way that serves to control the system itself or other systems associated with a process. Control system implemented must provide benefits, in this case able to increase the effectiveness and efficiency of the implementation of parking fees in Sidoarjo. Control in question is in terms of internal control monitoring. This study used qualitative methods, data obtained based on interviews and secondary data obtained at the time of the study with relevant stakeholders subscribe parking enforcement and the interview results were processed and analyzed later deduced to answer research questions. Keywords: control system, retribution subscription.